Private Paris - Patterson, James, 1947-; Sullivan, Mark T. (New York, NY : Little, Brown and Company, 2016)
When Jack Morgan stops by Private's Paris office, he envisions a quick hello during an otherwise relaxing trip filled with fine food and sightseeing. But, he is quickly pressed into duty after a call from his client Sherman Wilkerson, asking Jack to track down his young granddaughter who is on the run from a brutal drug dealer.
Keywords: Private investigators -- Fiction; Large type books; Paris (France) -- Fiction; Suspense fiction